COMPARATIVE ANALYSIS OF MEDICAL AND SURGICAL MANAGEMENT OF ECTOPIC PREGNANCY - KHAN, AGM; KAKAR, PK; AULAKH, FHM; TOFAIL, S; BASHIR, M (Biological and Clinical Sciences Research Journal, 2024)
A pregnancy that occurs in any place other than the endometrial cavity is called ectopic pregnancy. Objectives: The main aim of the study is to find a comparative analysis of medical and surgical management of ectopic pregnancy. Methods: This retrospective study was conducted at Hospital Civil/SPH Quetta. from January 2023 to December 2023. Data was collected from 220 patients. Comprehensive clinical and demographic data were extracted from electronic medical records. These included patient age, gravidity, parity, gestational age at diagnosis, presenting symptoms, imaging results, serum β-hCG levels, treatment modalities utilised, procedural specifics, and post-intervention outcomes. Results: Data were collected from 220 patients suffering from ectopic pregnancies. The mean age of patients in the medical management group was 29.2±4.3 years, and 29.8±4.1 years in the surgical management group. Nulligravid patients were more prevalent in the medical management group (58%) compared to the surgical management group (45%), while multigravida patients were more evenly distributed between the two groups (42% vs. 55%). In comparing medical and surgical management of ectopic pregnancy, surgical management demonstrated a higher success rate (95%) compared to medical management (85%). Medical management with methotrexate typically resolved ectopic pregnancies within an average of 17 days, whereas surgical interventions varied in time to resolution. However, surgical management had a slightly higher complication rate (12%) than medical management (10%). Conclusion: It is concluded that both medical and surgical management options demonstrate high efficacy in resolving ectopic pregnancy, with considerations for individual patient characteristics and clinical presentations.